2018
DOI: 10.1038/s41593-017-0044-6
|View full text |Cite
|
Sign up to set email alerts
|

Social transmission and buffering of synaptic changes after stress

Abstract: Stress can trigger enduring changes in neural circuits and synapses. The behavioral and hormonal consequences of stress can also be transmitted to others, but whether this transmitted stress has similar effects on synapses is not known. We found that authentic stress and transmitted stress in mice primed paraventricular nucleus of the hypothalamus (PVN) corticotropin-releasing hormone (CRH) neurons, enabling the induction of metaplasticity at glutamate synapses. In female mice that were subjected to authentic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 44 publications
10
147
1
Order By: Relevance
“…In mice, the induction of hyperalgesia in this case occurs at least partially via olfactory cues, as naïve mice exposed only to the bedding of conspecifics that were undergoing bouts of painful alcohol withdrawal displayed similar increases in their pain sensitivity . Similarly, naïve rodents that interact with a stressed conspecific display a host of abnormalities in endocrine production and behavior and even show changes in synaptic plasticity . Olfactory signals also serve to transmit information about desirable environmental stimuli such as safe food sources.…”
Section: Modes Of Communication Important To Social Learningmentioning
confidence: 99%
“…In mice, the induction of hyperalgesia in this case occurs at least partially via olfactory cues, as naïve mice exposed only to the bedding of conspecifics that were undergoing bouts of painful alcohol withdrawal displayed similar increases in their pain sensitivity . Similarly, naïve rodents that interact with a stressed conspecific display a host of abnormalities in endocrine production and behavior and even show changes in synaptic plasticity . Olfactory signals also serve to transmit information about desirable environmental stimuli such as safe food sources.…”
Section: Modes Of Communication Important To Social Learningmentioning
confidence: 99%
“…A simple model is that pathways transmitting different types of information converge on the central “integrator‐neurons.” However, the multimodal nature of incoming information is more likely to require that the distributed groups of brain nodes, responsible for each modality, operate the integrations through the hierarchical connections and undergo opposing adaptations in response to fear buffering and fear enhancing cues. As one of the nodes, Sterley et al have found such properties in the hypothalamic corticotropin‐releasing hormone neurons, which acquired short‐term plasticity in mice that were footshocked or interacted with a distressed conspecific, but lost the plasticity after the animal interacted with the naïve conspecific that buffered fear . Thus, the CRH neurons participate in integrating the competing effects from aversive and appeasing social signals.…”
Section: Future Directions: Search For Neuronal Mechanisms To Integramentioning
confidence: 99%
“…Two studies with rodents (Barr & Phillips, ; Kleen, Sitorner, Killeen, & Conrad, ) and one study with humans (Shinto, ) reveal a negative association between individual general stress and motivation, although the quality of motivation is neglected. Furthermore, little is known about how classmates' general stress affects an individual's stress level and/or motivation, although recent neuroscientific findings have shown that stress can be “contagious,” with behavioural and hormonal consequences of stress transmitted to others (Sterley et al, ).…”
Section: General and Academic Stress And Motivationmentioning
confidence: 99%
“…With the aim to fill this research gap, the present study examines the association between the student's general stress perception and the four indicators of the quality of motivation: intrinsic motivation, extrinsic motivation, learning goal orientation, and avoidance achievement goal orientation. According to recent neuroscientific findings (Sterley et al, ) and COR, classmates' average general stress level is considered a predictor of a student's quality of motivation, assuming that the level of the student's general stress can only be understood as a result of his or her experiences with social others (Hobfoll, ). Furthermore, differences between students from low‐tracking schools and students from high‐tracking schools in the association between stress and motivation are considered.…”
Section: General and Academic Stress And Motivationmentioning
confidence: 99%